Fuse blow scheme and its impact on overhead distribution system reliability - Bajerai, Qaddafi Abdullah (2014)
Electricity has become a major necessity in the modern world, and the availability has to reach to not only the city area but to the rural areas of population as well. To ensure the electrical distribution system is healthy, protection schemes have to be in place and one such method is the use of fuse blow method. This method is extensively used by the electric utility’s distribution system in Sabah and has shown effective protection requirements. However, this comes as a tradeoff to customers experiencing outages of electric supply. The study was carried out to identify the impact of fuse blow method and the accompanying results from actual performance of the overhead distribution system in a selected area, which in this case is the Kota Belud area. Many factors influence the reliability of the system such as the length of the distribution feeders, number of customers in each point of the system and placement of the fuses. The method used was the enumerative analysis to calculate the reliability impact of the fuse blow method. From the calculations, the result is then compared with the actual performance of the system in a one year period. The length of the feeders has the biggest impact to the reliability calculation and this is reflected by the data of actual performance of the feeders. A delicate balance of fusing coordination and limiting of feeder length is needed to ensure that the impact of the fuse blow method to the customer is adequately mitigated.